OC-009 Withdrawal of anti-tnf following sustained remission for inflammatory bowel disease: a systematic review and meta-analysis. (22nd June 2015) - Kennedy, NA; Lindsay, JO; Gordon, J; Hart, A; McCartney, S; Irving, P; Satsangi, J; Lees, CW
Abstract : Introduction: UK regulators mandate reassessment of disease activity after 12 months of anti-TNF therapy for Crohn's disease (CD), with consideration of withdrawal of treatment. There is a need for more data to establish the rates of relapse following treatment cessation. We have therefore analysed an expanded retrospective cohort of patients from the UK and performed a systematic review and a meta-analysis of all available literature. Method: Our original cohort of 80 UK IBD patients 1 was expanded to 161 accurately phenotyped subjects (142 CD, 19 ulcerative colitis [UC]/IBD unclassified). Searches were conducted of PubMed and EMBASE to identify all other published studies or conference abstracts that described outcomes after drug withdrawal for sustained clinical remission. Studies were excluded where patients had not had maintenance therapy for ≥12 months or where it was not possible to ascertain the relapse rate at 12 months. Data regarding relapse rates and response to retreatment were extracted and combined using a random-effects meta-analysis. Results: After removal of duplicates, 2371 studies were identified with initial searches. 12 studies were included in the final meta-analysis with 697 CD patients and 132 UC/IBDU. For CD, the estimated 1-year relapse rate was 0.38 (95% confidence interval [CI] 0.34–0.43); see forest plot in Figure 1 . Heterogeneity was low. Data on retreatment with anti-TNF was available for 188 patients. The estimated chance of retreatment success was 0.95 (95% CI 0.92–0.98). For UC/IBDU, the estimated 1-year relapse rate was 0.34 (95% CI 0.26–0.42) and retreatment success was estimated as 0.92 (95% CI 0.86–0.98). Conclusion: Remarkably consistent data has now emerged that supports relapse rates in CD and UC of just over a third by one year after discontinuation of anti-TNF maintenance for sustained remission. Although some indicators show promise, prediction of relapse remains challenging. Disclosure of interest: None Declared. Reference: Kennedy NA, Warner B, Johnston E, et al . OC-001 Anti-tnf withdrawal in Ibd: initial results from a pan-UK study. Gut 2014;63 :A1